Typology and Life Style Analysis of the Raft House (Ruan Pae) in Riverine Settlements in Thailand - Denpaiboon, Chaweewan; Tohiguchi, Mamoru; Matsuda, Hiroyuki; Hashimoto, Seiyu (Journal of Architectural/Planning Research and Studies (JARS), 2002)
This paper describes two areas concerning raft houses in Thailand for the purpose of (1) the classification of the raft house typology, measured by field surveys and mapping, and (2) the study of the way of life of the inhabitants and their satisfaction towards living in the raft houses, as well as the conditions of the raft house settlements, as researched by questionnaires and in-depth interviews. This study encompasses three subareas of study including (1) the physical features of the raft houses, (2) the way of living in them, and (3) the coexistence of the inhabitants, water and land. It is found that: (1) the typological features are varied by location, function and life style, (2) the conditions of the inhabitants in the raft houses are insecure for today’s living, (3) the existence of the raft house communities depends on the coexistence of the environments of water and mankind.